PENERAPAN MODEL PEMBELAJARAN THINK PAIR SHARE UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA - Sudirman, Sudirman (Jurnal Pendidikan Fisika, 2016)
Learning science in junior high school raises many problems found on direct instruction, students learn such activity is very low. Students lacking the spirit to learn science, pretend to understand the teachers explanations. Students in learning activities mediocre both classical learning and teamwork that ultimately student learning outcomes many incompletes. To overcome this, then do action research in order to improve the results of junior high school students learn science through learning model Think Pair Share for Class VIII.1 second-semester students of SMP Negeri 2 Metro in the academic year 2012/2013. This study time is 3 months. Based on the recapitulation of the data observation learning process and the work of the group, the student learning outcomes can be summarized as follows. In observation of the learning process from the first meeting until the meeting of the 6th, there is increased an activity of students in learning. This happened after learning that teachers undertake improvements at each meeting.